Acceptance Analysis of the Electronic Kohort Information System for Maternal and Child Health Using the Technology Acceptance Model at the Bima City Health Center - Hizriansyah; Shinta Prawitasari; Lutfan Lazuardi (Jurnal Sistem Informasi, 2023)
The Maternal and Child Health (MCH) Program in Indonesia is faced with a diversity of achievements between regions caused by disparities in the capacity of the health system and exacerbated by the Covid-19 pandemic which has caused a decrease in service activities and reporting quality so that digitalization of services is needed. This type of research is qualitative research with the design of phenomenological studies using thematic analysis with the help of the Nvivo 12 application. Primary data collection was carried out by means of observation and in-depth interviews with research informants by purposive sampling. To increase the credibility of the data use source triangulation. The research informants consisted of the head of the family health services section, the head of the health centers and the midwife as the user of the e-cohort. Thirteen informants (11 women and 2 men) participated in the study. Most informants can use the core functions of the e-cohort app navigation menu. The study proposes that the perceived perception of ease of use may not be in line with the perceived expediency of explaining variations in the successful acceptance of MCH e-cohort applications. The study also found that there were differences in outcomes between user perceptions at the operational level and policy makers at the managerial level. In general, the analysis collects several types of obstacles and potentially problems that negatively affect the usefulness of the e-cohort application : not being able to make the work of midwives easier and faster, ineffective and not so much to increase the productivity of performance. With regard to ease of use, users feel that the e-cohort can be easily learned and used. The e-cohort is considered to have value as a system that makes the work of midwives more difficult and hinders the work, however, the appearance, elements, features and design are perceived to be quite easy to use. In addition, users also highlight the need to consider how the system can be implemented in order to minimize the impact and optimize usability